The Role of Women in Improving Family Resilience in The Middle of The Covid-19 Pandemic - Setyasih Harini; Damayanti Suhita; Andri Astuti Itasari (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2020)
Coronavirus is a deadly threat to all humankind. Its sudden arrival confused the government and society. The government policy, which limits activities outside the home and demands people to avoid crowds, followed by learning from home, is a new burden for the community. This article aims to explain a mother’s new role as a teacher and build more effective family communication patterns in dealing with Covid-19. The research was carried out by collecting data from several respondents who live in the Surakarta area. This article’s object is related to the activities of mothers who are also online teachers to their children at home with different educational backgrounds and social statuses. This study’s results show that the Covid-19 pandemic was an opportunity for women as citizens and citizens to experience social change. First, related to the globalization vortex that is increasingly aggressively forcing women to come into contact with information technology more. Women, namely mothers, are invited to better understand user information technology to become teachers and accompany their children when learning from home. Second, this period at the same time provides an opportunity for Javanese women to further instill social moral values as provisions for their children in the future. Third, this period is an opportunity to improve ourselves so that they are more worthy of becoming a more meaningful creature.